Evaluasi Atas Harga Pokok Produk Sampingan Dalam Kaitannya Dengan Perhitungan Laba Perusahaan: Study Kasus pada CV. Morinda House Bogor - Setiawan, Hendra; Lisias, Victor (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2009)
The goal of this research is to find out production process and integrated cost, productions cost of secondary product, and cost price influence of secondary product towards companyâs profit. The research yield shows that CV Morinda House divided production cost into two categories, namely direct costand inderect cost. Based on main function of the company, CV Morinda House arranged production cost into three categories, namely basic material cost, direct man-power cost, and factory overhead cost. Besides that, secondary product at CV Morinda House was processed more until becoming capsule product. The company did not allocate integrated cost, but focused to how to treat selling yield of its secondary product. Key words: production process; Secondary product; companyâs profit